Norway rat (Rattus norvegicus) ectoparasites in livestock production systems from central Argentina: influencing factors on parasitism - Alonso, Rodrigo Javier (2019)
Haematophagous ectoparasites are worldwide vectors of many zoonotic bacterial diseases, both emerging and re-emerging, whose incidences are rising. Livestock development alters different environmental characteristics such as the microclimate of a site, changing the availability, density and susceptibility of the hosts to pathogens and vectors, indirectly influencing the spread and persistence of a disease within an ecosystem. The Norway rat (Rattus norvegicus), the most abundant vertebrate pest species found on livestock farms from Argentina, is a reservoir for several important zoonotic bacteria and may harbor ectoparasite species, which act as their vectors. Even though the Norway rat is widely known for its role as an ectoparasite host, the ecological characteristics of their ectoparasite communities and the related factors with parasitism on livestock farms have never been described. In the present study, we describe the ectoparasite community in Norway rats from central Argentina livestock farms, while also depicting the influencing factors on both ectoparasite occurrence and abundance. Ectoparasites were collected from rats captured in 20 sites from Buenos Aires province, between the winter of 2016 and the summer of 2018. A total of 1441 ectoparasite individuals were collected from 159 Norway rat individuals [Total ectoparasite prevalence = 69.2%; Mean ectoparasite specimen abundance (± CI) = 9.06 ± 2.32 ectoparasite individuals per rat; Mean ectoparasite specimen intensity (±CI) = 13.10 ± 3.08 ectoparasite individuals per infested rat found]. Ectoparasite assemblage consisted of four cosmopolitan species, recognized for their sanitary relevance: mites (Laelapidae: Laelaps nuttalli and Laelaps echidninus), lice (Polyplacidae: Polyplax spinulosa) and fleas (Pulicidae: Xenopsylla cheopis). We observed higher Norway rat abundance in sites related to higher ectoparasite occurrence and abundance frequencies on the rats. Additionally, ectoparasites were more abundant on rats in warm seasons and on male individuals, over female rats. Moreover, the geographical location of the studied sites influenced the ectoparasite assemblage structure observed on the rats. This study broadens the knowledge on the role of Norway rats as zoonotic ectoparasites hosts and analyzes the drivers influencing ectoparasite occurrence and abundance on the most populated region of Argentina, which is also the region with the most intensive livestock farming. Therefore, this survey may assist in evaluating potential risks for humans and generate effective sanitary control strategies for ectoparasite-borne infectious diseases.